Pengaruh Rasio Early Warning System dan Good Corporate Governance terhadap Tingkat Solvabilitas pada Asuransi Jiwa Syariah - Julietta Fairuzar Awrasya; Kusumaningtias, Rohmawati (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
The purpose of this research is to determine the effect of early warning systems (EWS) and good corporate governance (GCG) on the level of solvency. The indicators that used to measure EWS are the ratio of the change in surplus, the ratio of claim expenses, the ratio of management fees, the ratio of liquidity and the ratio of premium growth. Meanwhile, the indicators used to measure GCG are the size of the board of commissioners, the size of the board of directors and the size of the sharia supervisory board (SSB). The indicator used to measure the level of solvency is risk based capital (RBC). This research uses a quantitative research method with purposive sampling technique, which produces a sample of 14 sharia life insurance companies (consisting of 70 data) listed in the Financial Services Authority for the 2015-2019 period. This research has results that show that the ratio of changes in surplus, the ratio of claim expense, the ratio of management costs, the ratio of premium growth, and the size of SSB have no influence on the level of solvency. Meanwhile, the liquidity ratio, the size of the board of commissioners and the size of the board of directors have an influence on the level of solvency.